IDENTIFICATION AND MINIMIZATION OF RISKS TO THE ECONOMIC SECURITY OF THE ENTERPRISE - BOHDANIUK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The modern business environment is characterized by a high level of uncertainty, which creates numerous threats to the stable functioning of business. Effective risk management is an essential element of the economic security system, which allows enterprises to avoid negative consequences and maintain a competitive position in the market. Risk reduction is essential to an economic security strategy because it creates a sustainable management system that can adapt to rapidly changing conditions. This not only avoids crises but also increases business flexibility, helps to improve reputation, and strengthens positions in the market. The problem of reducing risks in carrying out financial and economic activities is still relevant for every enterprise, regardless of its type of activity, due to the growth of various threats in an unstable macroeconomic environment. To ensure sustainable development, the enterprise has to overcome various risk situations in modern conditions. To ensure a stable position, it is necessary to neutralize the risks of loss of invested resources and economic viability. The impact of risks on the economic security of the enterprise is significant, but timely identification and effective risk management can minimize their impact. Risk assessment of the enterprise's economic security is a process of identifying and ranking priorities, which requires a comprehensive analysis of information about possible threats and vulnerabilities to assess the potential impact of particular circumstances or events on the enterprise's activities. Developing a comprehensive risk management system will allow the enterprise to ensure stability and competitiveness in the market despite high uncertainty. Introducing modern analytical methods and tools helps to increase the accuracy in identifying potential threats and responding promptly. The article is aimed at researching the processes of identifying risks, analyzing their potential impact on financial and operational stability, and developing a system of measures that will contribute to ensuring the economic stability of the enterprise in conditions of internal and external threats.
Keywords: risk; minimization; security; threats; environment; resources